Business process mining for industry: successes and caveats - Mehnen, Jorn; Turner, Christopher J.; Tiwari, Ashutosh (Cranfield University, 2010)
Business Process Mining (BPM) is a powerful technique which aims at mapping the complex structure of industrial processes into human interpretable graph structures by analysing business process traces automatically. The transfer of an innovative idea into an industrially viable product is a challenging task in its own rights. First, this paper introduces the concept of business process mining and an innovative Genetic Programming (GP) approach. Second, this paper addresses the principal caveats and solutions that come with transferring new academic solutions into real-world applications. A real BPM transfer project serves a background for this discussion.
Keywords: Business Process Mining, Experience, Commercialisation of Software, Academia and Industry